Rapid detection of Tulipalin A with SESI-Orbitrap MS: an exploration across spring flowers - An N. T. Phan; Roy Eerlings; Hendrik G. Mengers; Lars M. Blank (Plant Methods)
Abstract Background Allergic contact dermatitis and chronic actinic dermatitis are frequently observed among florists and gardeners due to exposure to potentially allergenic plants and plant products. Tulipalin A, an alpha-methylene-gamma-butyrolactone, is a common allergen synthesized by Tulipa genera, but its natural occurrence across Plantae remains unexplored. Results Here, we demonstrated the secondary electrospray ionization coupled Orbitrap mass spectrometry (SESI-Orbitrap MS) methodology for quantifying tulipalin A release from plants upon injury. By outlining temperature treatment, homogenization strategies and plant organ distribution, we show that processing flower samples stored at room temperature using a garlic press yielded the highest tulipalin A release upon injury. Via real-time monitoring, tulipalin A release was demonstrated to occur immediately upon homogenization. Next, the biosynthesis of tulipalin A across spring flowers was landscaped. Highlighting Rosa, Gerbera, Neapolitanum, Ranunculus, Othocalis, Muscari, Galanthus, Tulipa and Alstroemeria to release detectable amounts of tulipalin A upon injury. Tulipalin A was predominantly released from the Tulipa and Alstroemeria species, both belonging to the Liliales order, as stated in previous clinical and research studies. Conclusions In conclusion, a rapid method using the SESI-Orbitrap MS is reported to detect and track tulipalin A synthesis across plant organs and outline its cross-species distribution. Our methodology can be easily adapted for mapping other volatile plant defense metabolites and identify potentially allergenic plants. By addressing these aspects, we can ensure a safer work environment for florists and gardeners.